Avaliação do processo de obtenção de farinha da casca de banana (Musa sapientum) das variedades Prata, Pacovan e Maçã - Pessoa, Thayze Rodrigues Bezerra (2009)
This work aimed to study the drying process of banana (Musa sapientum) peels (varieties Prata, Pacovan and Apple). The convective drying was performed at various air temperatures (40°C to 60°C) and at an average air speed of 1.0 m/s. It was used a fixed bed dryer with upward flow of air. The tests were conducted until the sample reached equilibrium between its own moisture and the drying air humidity. The drying kinetics was evaluated by the Fick, empirical two parameters exponential and Page semi-empirical models. From these models were found the water diffusivities. They were in the order of 10-10m/s². Overall diffusivities increased with drying air temperature. The highest drying rates were obtained for the banana peels from varieties Apple, Prata and Pacovan, respectively. Final product quality was evaluated through the following analysis: enzymatic activity, minerals and water activity. The best drying condition, which generated a final product with better quality, was at 60°C of air temperature for the three varieties.